REGULASI DIRI SANTRI PROGRAM TAHFIDZ DALAM PEMBELAJARAN DARING DI TENGAH PANDEMI COVID-19 - Gadis Deslinda; Musa Asy’arie; Taufik Taufik (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2022)
The Covid-19 outbreak requires all elements of education to adapt to the learning process carried out by distance education which has never been implemented before. Learning with the online system faced by students who memorize the Al-Quran will have an impact on their memorization targets. The purpose of this study is to reveal a more in-depth picture of self-regulation in tahfidz program students when participating in online learning amid the Covid-19 pandemic, and to reveal internal and external factors that can support and hinder self-regulation of tahfidz program students in online learning in the midst of the Covid-19 pandemic. This research is a qualitative research with a phenomenological study approach. The subjects in the study amounted to 9 students of the tahfidz program who did online learning. Determination of the sample in this study using purposive sampling technique. Data collection techniques were carried out by means of observation and interviews. Data analysis by means of data collection, data reduction, data presentation and drawing conclusions.The results of the study stated that students who memorized the Koran had good self-regulation by motivating themselves in memorizing the Koran to get closer to Allah SWT by carrying out obligatory and sunnah practices in an istiqomah manner and giving the best for their parents, students managing their emotions by telling stories to people who he trusts and believes that this pandemic is a test from Allah SWT, in strategy and self-management, students arrange daily activities at home with online memorization and murojaah deposit schedules. For students, parental support and a conducive family environment when online learning is very much needed so that they can regulate themselves better, the absence of an ustadz role model, the absence of direct rewards and punishments and the absence of friends in the struggle in a murojaah group in online learning make students less passionate (spirit) so that there is a reduced atmosphere of solemn mysticism in online memorization deposits. The students' self-evaluation ability is shown by a wiser attitude in dealing with exams, one of which is the exam during the COVID-19 pandemic.